Analysis of Thematic Books for Elementary School Students 2013 Curriculum in Gender Perspective - Sitti Jauhari; Sulfasyah Sulfasyah; Haslinda Haslinda (Institut Agama Islam Negeri Palopo, 2022)
The patriarchal view that has taken root in society is difficult to remove. Gender bias still occurs in various forms and situations, even though it is not realized. This study aims to determine the gender representation and bias in the thematic books of fourth graders of elementary school curriculum 2013 through quantitative descriptive content analysis. This study analyzes the frequency of representation and gender bias in fourth-grade thematic books. The sample in this study was the thematic book for fourth-grade students in the 2013 curriculum, theme 1 to theme 5. The data analysis technique in this study refers to the content analysis scheme according to Kripendorf with stages (1) unitizing (data collection); (2) sampling (sampling); (3) recording (recording/recording); (4) reducing (data reduction); (5) inferring (concluding); (6) narrating (narrative). The analysis results show that (1) gender representation in the fourth-grade thematic books is dominant to boys; (2) there is a gender bias in students' thematic books, which include gender bias on work roles, character values, social status, and hobbies.